INTRODUCTION TO HINDU ETHICS THROUGH BALI’S ORAL TRADITION IN THE CONTEXT OF HUMANISTIC EDUCATION FOR EARLY CHILDHOOD STUDENTS AT UDYANA KUMARA I TAMAN KINDERGARTEN - I Putu Suyasa Ariputra; Encep Syarief Nurdin; Yadi Ruyadi; Kadek Aria Prima Dewi PF; Bunyamin Maftuh; Momod Abdul Somad (Pratama Widya: Jurnal Pendidikan Anak Usia Dini, 2025)
Character education in the Alpha Generation era faces complex challenges due to rapid technological developments that influence children’s social interactions and personality formation. To address this, educational institutions must strengthen humanistic character education rooted in local culture from an early age. This research explores the transformation of Hindu ethical values through Balinese oral traditions: masatua (storytelling) and madolanan (traditional games) in early childhood education. Using a qualitative ethnopedagogical design, the research examines meanings, symbols, and local wisdom-based learning practices at Udyana Kumara I Taman Kindergarten. Data were collected through participatory observation, in-depth interviews, document analysis, and were analyzed reflectively through triangulation. The findings show that Balinese oral traditions are highly effective for introducing Hindu ethics, particularly Tri Kaya Parisudha values, through symbolic narratives, reflective dialogue, and participatory emotional experiences. Teachers play a key role as humanistic facilitators who create meaningful, contextual, and joyful learning environments. Theoretically, this research enriches applied ethical philosophy in character education; practically, it highlights the need for teachers’ humanistic pedagogical competence; and culturally, it supports the preservation of Balinese heritage as a strategy for early character formation. Thus, Balinese oral traditions serve as relevant and effective media for teaching ethical virtues within a humanistic education framework. .